THE INFLUENCE OF BRAND IMAGE ON THE PURCHASE DECISION OF MOMOYO PRODUCTS BY STUDENTS OF THE FACULTY OF ECONOMICS AT UNIMED - Dewi Larasati Sinaga; Abed Nego Siregar; Fitry Ulinda Tinambunan; Sarah Lylia Saragi; Veranita Sitio; Yefoni Banjarnahor (Outline Publisher, 2025)
This study aims to analyze the influence of brand image on purchasing decisions of Momoyo products among students of the Faculty of Economics, State University of Medan (UNIMED). Using quantitative methods and descriptive approaches, data were collected through online questionnaires from 32 randomly selected respondents. Validity, reliability, normality tests, and simple linear regression analysis were used to analyze the data. The results showed that brand image has a positive and significant influence on purchasing decisions, with a regression equation of ￼. The regression coefficient of 1.145 indicates that every one unit increase in brand image increases purchasing decisions by 1.145 units. The Cronbach's Alpha value of 0.935 indicates excellent instrument reliability, while the normality test with a significance value of 0.200 ensures that the residuals are normally distributed.